White blood cells, monocytes and thrombin time in predicting symptomatic hydrocephalus in patients with aneurysmal subarachnoid hemorrhage - Deng, Hui; Yang, Hongjuan; Chen, Ruoyu; Xing, Wei; Shi, Jia (Frontiers in Surgery, 2025)
ObjectiveTo investigate the value of admission blood routine and coagulation function parameters in predicting acute symptomatic hydrocephalus in patients with aneurysmal subarachnoid hemorrhage (aSAH).MethodsThis retrospective study included 423 patients with aSAH admitted to the Department of Neurosurgery of the Third Affiliated Hospital of Soochow University from November 2013 to September 2020. Demographic, clinical and laboratory data were collected. The patients were divided into hydrocephalus group (n = 96) and non-hydrocephalus group (n = 327) according to the presence of hydrocephalus on the first head CT. Univariate and multivariate logistic regression analyses were used to determine the independent risk factors for acute symptomatic hydrocephalus after aSAH.ResultsAmong the 423 aSAH patients, 96 (22.70%) developed acute symptomatic hydrocephalus. Multivariate logistic regression analysis showed that, after adjusting for confounding factors, white blood cells (WBC) (OR = 1.121, 95% CI = 1.067–1.181), monocytes (M) (OR = 2.812, 95% CI = 1.183–6.699), and thrombin time (TT) (OR = 0.843, 95% CI = 0.729–0.948) were independently associated with the development of hydrocephalus. Further analysis of the area under the receiver operating characteristic (ROC) curve indicated that, compared to basic clinical data, the combined prediction model of “basic clinical data + WBC + M + TT” performed better (AUC = 0.728, 95% CI = 0.682–0.769, P = 0.004).ConclusionsThe WBC, M and TT within 24 h of admission in aSAH patients can be used to predict the occurrence of acute symptomatic hydrocephalus.